2018
DOI: 10.1080/21691401.2018.1470526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SiO2/Au core–shell nanoparticles on breast cancer cell’s radiotherapy

Abstract: Based on the results of the study it can be concluded that the gold-silicon oxide shell-core NPs could play an effective role in radiotherapy of MCF-7 breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The nuclear fragmentation and disintegration is a characteristic of apoptosis [42]. There are also several studies which have reported the use of DAPI as early indicator of apoptotic cell death [42][43][44][45]. We do not know the mechanism of action of FMSP-nanoparticles in eliciting cell death, the possibility of apoptotic pathways cannot be ruled.…”
Section: Discussionmentioning
confidence: 96%
“…The nuclear fragmentation and disintegration is a characteristic of apoptosis [42]. There are also several studies which have reported the use of DAPI as early indicator of apoptotic cell death [42][43][44][45]. We do not know the mechanism of action of FMSP-nanoparticles in eliciting cell death, the possibility of apoptotic pathways cannot be ruled.…”
Section: Discussionmentioning
confidence: 96%
“…SiNPs are less toxic in, possibly due to a higher adsorption by tissues, however, at high concentrations, in vitro toxicity includes pro-inflammatory responses, oxidative stress, and autophagy [25]. Gold-silicon composites show acceptable toxicity and good biocompatibility [26].…”
Section: Introductionmentioning
confidence: 99%
“…The SiO 2 NPs were synthesized based on the sol-gel method reported previously [62,63]. In the next step thiol-functionalized silica-coated nanoparticles (TFSNPs) were prepared according to the method mentioned in our previous study [64]. The Au nanoparticles were produced by a citrate reduction method (Turkevich method) [65].…”
Section: Preparation Of Au@sio 2 Nanoparticlesmentioning
confidence: 99%
“…The cells exposed to only laser irradiation (without NPs) and the cells without any NPs and laser treatments considered as positive and negative control, respectively. After 24 h of laser irradiation the cell viability was measured by MTT assay method [64].…”
Section: In Vitro Laser Therapymentioning
confidence: 99%